Widespread mineralization of soft‐bodied insects in Cretaceous amber. Issue 3 (24th February 2022) - Jiang, Hui; Tomaschek, Frank; Drew Muscente, A.; Niu, Changtai; Nyunt, Thet Tin; Fang, Yan; Schmidt, Ute; Chen, Jun; Lönartz, Mara; Mähler, Bastian; Wappler, Torsten; Jarzembowski, Edmund A.; et al.
Abstract: Fossilized tree resin, or amber, commonly contains fossils of animals, plants and microorganisms. These inclusions have generally been interpreted as hollow moulds or mummified remains coated or filled with carbonaceous material. Here, we provide the first report of calcified and silicified insects in amber from the mid‐Cretaceous Kachin (Burmese) amber. Data from light microscopy, scanning electron microscopy (SEM), energy‐dispersive and wavelength‐dispersive X‐ray spectroscopy (EDX and WDX), X‐ray micro‐computed tomography (Micro‐CT) and Raman spectroscopy show that these Kachin fossils owe their preservation to multiple diagenetic mineralization processes. The labile tissues (e.g. eyes, wings and trachea) mainly consist of calcite, chalcedony and quartz with minor amounts of carbonaceous material, pyrite, iron oxide and phyllosilicate minerals. Calcite, quartz and chalcedony also occur in cracks as void‐filling cements, indicating that the minerals formed from chemical species that entered the fossil inclusions through cracks in the resin. The results demonstrate that resin and amber are not always closed systems. Fluids (e.g. sediment pore water, diagenetic fluid and ground water) at different burial stages have chances to interact with amber throughout its geological history and affect the preservational quality and morphological fidelity of its fossil inclusions.